2021
DOI: 10.1111/srt.13090
|View full text |Cite
|
Sign up to set email alerts
|

Antiwrinkle efficacy of 1‐ethyl‐βN‐acetylglucosaminide, an inducer of epidermal hyaluronan production

Abstract: Background Hyaluronan (HA) has a unique hydration capacity that contributes to firmness and bounciness of the skin. Epidermal HA declines with skin aging, which may lead to clinical signs of aging including skin wrinkles and loss of hydration and elasticity. Recently, we developed a new cosmetic agent 1‐ethyl‐β‐N‐acetylglucosaminide (β‐NAG2), which enhances HA production in cultured human keratinocytes. The aim of this study was to explore antiaging potential of β‐NAG2 in reconstructed human epidermal models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Therefore, it is tempting to speculate that HAS3-mediated HA production, rather than the extracellular level of epidermal HA, may be linked to epidermal organization and function, including keratinocyte proliferation and differentiation, at least in the developing epidermis in reconstructed epidermal equivalents. This notion is supported by our previous findings that 1-ethyl-β-N-acetylglucosaminide, an inducer of HAS3-mediated HA production [21], caused epidermal thickening by accelerating keratinocyte proliferation and differentiation [22,23]. However, since small HA oligosaccharides, which are known to induce keratinocyte proliferation and differentiation [36,37], could not be measured with the HA ELISA assay, we cannot exclude the possibility that changes in HA size by St-HAase treatment may influence epidermal organization and architecture.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it is tempting to speculate that HAS3-mediated HA production, rather than the extracellular level of epidermal HA, may be linked to epidermal organization and function, including keratinocyte proliferation and differentiation, at least in the developing epidermis in reconstructed epidermal equivalents. This notion is supported by our previous findings that 1-ethyl-β-N-acetylglucosaminide, an inducer of HAS3-mediated HA production [21], caused epidermal thickening by accelerating keratinocyte proliferation and differentiation [22,23]. However, since small HA oligosaccharides, which are known to induce keratinocyte proliferation and differentiation [36,37], could not be measured with the HA ELISA assay, we cannot exclude the possibility that changes in HA size by St-HAase treatment may influence epidermal organization and architecture.…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, the reduction in epidermal HA by the HA synthesis inhibitor 4-methylumbelliferone (4MU) in organotypic cultures of rat keratinocytes or by a deficiency in the cell surface HA receptor CD44 in mice led to decreased keratinocyte proliferation and differentiation, respectively [ 19 , 20 ]. Furthermore, we recently reported that enhanced epidermal HA production mediated by 1-ethyl-β- N -acetylglucosaminide, a new inducer of epidermal HA production [ 21 , 22 ], resulted in epidermal thickening by accelerating keratinocyte proliferation and differentiation in reconstructed human skin equivalents [ 23 ]. Therefore, epidermal HA is generally considered to boost epidermal proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%